Economic Waves: The Effect of the U.S. Economy on the World Economy - Mario Arturo Ruiz Estrada (Contemporary Economics)
This paper models the inter-connections between the U.S. economy and five major economic regions in the world, namely, Japan, China, ASEAN, Latin America, and the European Union, using an inter-linkage coordinate space. This space is represented graphically, with the U.S. economy placed in the center and the connected economic regions plotted along rays (axes) that are drawn from the center, each of which can have as many windows as are required at the predetermined perimeter levels. Using this model, this paper evaluates whether and how an economic recession or financial crisis in the U.S. economy can simultaneously affect the five aforementioned economic regions. Finally, this paper proposes the use of computer graphical animation to provide a visual representation of the concomitant effect of these economic waves in the same graphical space.